(untitled) (Journal of the Bangladesh Agricultural University, 2012)
To investigate the Epidemiology of Paramphistomum infection in cattle, faecal samples from 360 cattle were collected from individual areas of the Sirajgonj district from March 2009 to April 2010. One hundred and ninety one animals (53.1%) were infected with single or multiple species of Paramphistomum. Age of animals significantly (P<0.05) influenced the prevalence of Paramphistomiasis. Older animals suffered (60.3%) more than growing (44.4%) and young (54.0%) ones. Older animals were 1.94 times more susceptible than growing animals. Furthermore, females were more (59.5%; 1.79 times) susceptible to Paramphistamum spp. than males (45%). Breed has also significant (p<0.05) effect. The prevalence of Paramphistomiasis was higher (p<0.05) in crossbred (61.8%) animals than that of local (49.2%) cattle. The crossbreed cattle were 1.7 times more susceptible than indigenous cattle. The prevalence of Paramphistomiasis in cattle varied (p<0.05) depending on the season of the year; being highest in the rainy season (60.8%) followed by the summer (50%) and lowest during the winter (48.3%). A high percentage of paramphistomiasis was recorded in the cattle studied during the winter irrespective of age and genetics of animals and seasons of the year. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10992 J. Bangladesh Agril. Univ. 9(2): 229232, 2011